Numerical Treatment of short Laser Pulse Compression in transient stimulated Brillouin Scattering - Dement’ev, A.; Girdauskas, V.; Vrublevskaja, O. (Nonlinear Analysis: Modelling and Control, 2002)
Results of numerical investigation of the compression process of short pulses during essentially nonstationary SBS are presented, taking into account the diffraction and focusing of the interacting light beams and the finite oscillation period and lifetime of hypersound waves in nonlinear media.